(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality worldwide. The incidence of AMI is dependent on certain traditional predisposing risk factors. In addition to the traditional risk factors, raised serum calcium level is also being considered as an associated factor for AMI. The aim of the study is to evaluate the association of serum calcium level with acute myocardial infarction in a tertiary level hospital in Bangladesh. This case control study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from January 2013 to December 2013. In this study, 50 diagnosed cases of AMI and 50 age and sex matched apparently healthy subjects were selected from DMCH purposively according to the selection criteria. Blood pressure, height and weight were measured and BMI was calculated. Biochemical parameters- serum calcium and fasting blood glucose in two groups were estimated in mmol/l. Then serum calcium was compared between two groups to observe the association with AMI. Results were analyzed statistically in SPSS version 17.0. Unpaired student’s ’t’-test and Spearman correlation analysis was done. All the results were expressed as mean ±SD and p value <0.05 was accepted as level of significance. Present study showed that serum calcium level was significantly higher(p=.001) in cases (2.61±.15 mmol/l) when compared with that of controls (2.13±.15mmol/l). Serum calcium also showed a significant positive correlation with AMI (rho=0.858, p=0.001).Findings of study concludes that increased serum calcium is associated with AMI. Bangladesh J Med Biochem 2015; 8(1): 16-20